2014
DOI: 10.1103/physrevb.89.075123
|View full text |Cite
|
Sign up to set email alerts
|

Second-harmonic double-resonance cones in dispersive hyperbolic metamaterials

Abstract: We study the formation of second-harmonic double-resonance cones in hyperbolic metamaterials. An electric dipole on the surface of the structure induces second-harmonic light to propagate into two distinct volume plasmon-polariton channels: a signal that propagates within its own peculiar resonance cone and a phase-locked signal that is trapped under the pump's resonance cone. Metamaterial dispersion and birefringence induce a large angular divergence between the two volume plasmon polaritons, making these str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 48 publications
0
34
0
Order By: Relevance
“…Furthermore, from the above derivation suggests that the ENZ resonance is more advantageous for transmission than the ENP resonance, because the prefactor fullfills for ǫ > 0 typically |A| < 1. Note, that both regimes of ENZ and ENP were discussed in the context of diffraction suppressed hyperbolic lensing [44], using the canalization regime for hyperbolic lensing [72,73] and directed dipole emission [45]. In these cases, the advantage of using ENZ and ENP resonances lies in the resulting very flat iso-frequency line of the extraordinary modes so that the group velocity is mainly directed along the optical axis for a very broad band of lateral wavenumbers κ.…”
Section: Anomalous Transmission For Hyperbolic Materialsmentioning
confidence: 99%
“…Furthermore, from the above derivation suggests that the ENZ resonance is more advantageous for transmission than the ENP resonance, because the prefactor fullfills for ǫ > 0 typically |A| < 1. Note, that both regimes of ENZ and ENP were discussed in the context of diffraction suppressed hyperbolic lensing [44], using the canalization regime for hyperbolic lensing [72,73] and directed dipole emission [45]. In these cases, the advantage of using ENZ and ENP resonances lies in the resulting very flat iso-frequency line of the extraordinary modes so that the group velocity is mainly directed along the optical axis for a very broad band of lateral wavenumbers κ.…”
Section: Anomalous Transmission For Hyperbolic Materialsmentioning
confidence: 99%
“…It could be shown that they allow for a broadbandenhanced LDOS [3], broadband-enhanced spontaneous emission [4][5][6][7][8][9][10], hyperbolic lensing [11][12][13][14][15], negative refraction [16,17], super absorption [18], enhanced Förster energy transfer [19][20][21], and self-induced torques [22]. HM can be artificially fabricated by a periodic layout of subwavelength metal and dielectric components for applications in the visible.…”
Section: Introductionmentioning
confidence: 99%
“…Further advance was connected with the rapid development of hyperbolic metamaterials , which feature hyperbolic isofrequency contours and thereby support extremely large wave vectors. Unique dispersion of hyperbolic metamaterials proved useful for nonlinear processes . In particular, the advantages of hyperbolic dispersion, and of combining that with the normal dispersion at other frequencies, brought a new degree of freedom to realize phase matching in layered structures , potentially enabling the use of non‐conventional nonlinear dielectrics.…”
Section: Hyperbolic Dispersion For Nonlinear Phase Matchingmentioning
confidence: 99%